(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the everyday vocabulary of Russian and Uzbek languages from the perspective of socio-cultural interpretation. Semantic groups of words reflecting lifestyles, habits, and cultural traditions of the peoples are analyzed. The study is based on dictionaries, media texts, student writings, and observations. Differences and similarities in the use of everyday words, the influence of globalization and digital environment, and the adaptation of loanwords are identified. The work emphasizes the importance of considering the cultural context when studying everyday vocabulary and its teaching.